The contribution of forest remnants within industrial area to threatened mammal conservation: A case study in liquefied natural gas industry in Bontang, Indonesia - SUDRAJAT; MINTORO DWI PUTRO (Society for Indonesian Biodiversity, 2019)
Abstract. Sudrajat, Putro MD. 2019. The contribution of forest remnants within industrial area to endemic and threatened mammal conservation: A case study in liquefied natural gas industry in Bontang, East Kalimantan, Indonesia. Biodiversitas 20: 2257-2265. Tropical forests harbor high biodiversity, while natural protected area is one of the approaches for biodiversity conservation. However, the conversion of natural forests for various purposes has caused forest fragmentation. A novel strategy of conservation is proposed in the form of protected area within industrial estate as the contribution of industrial company in biodiversity conservation. The purpose of this study is to document the endemic and threatened species of mammals existing at two forest fragments with extent of 15 ha and 7.4 ha in a natural gas refinery industry area in Bontang, East Kalimantan and their potential as biodiversity conservation areas. Mammals were monitored at the two forest fragments through direct surveys, trace identification, mist nets, and camera traps. The results of the study show that according to IUCN Red List there were 23 mammal species (belonging to 18 genera, 15 families and six orders) of conservation concern found within the forest fragments including one species is under Critically Endangered, two are Endangered, four are Vulnerable, ten are Least Concern, one is Near Threatened and three are Not Evaluated. Four of those species are considered as endemic, namely Bornean orangutan, Pongo pygmaeus morio, Müller’s gibbon, Hylobates muelleri, Proboscis monkey, Nasalis larvatus and East Bornean slow loris, Nycticebus menagensis. These findings suggest that forest fragments located in the environment of industrial estate can be considered as important conservation strategy if they are well preserved and maintained.